Engaging Haiti: How Designers Facilitate Long-Term Disaster Recovery - Karl Johnson; Stacey McMahan (Oz, 2013)
There is a reason why Pétionville is the center of the recovery effort in Haiti. Its perch in the hills above Port-au-Prince offers relative isolation from the metropolis, in addition to the mind-boggling panoramic views of the basin and bay from which that city has grown—qualities enough for establishing a national financial center, and some of Haiti’s most luxurious hotels.